Pengaruh Pertumbuhan Perusahaan, Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Galuh Nilam Kusuma Wardani; Dwiyani Sudaryanti; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine and analyze the effect of company growth, profitability and capital structure, the effect of company growth on firm value, the effect of profitability on firm value, the effect of capital structure on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019 period -2021. This research was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period using the purposive sampling method and the samples used in the food and beverage sub-sector manufacturing companies listed on the IDX for the 2019-2021 period were 11 companies. Multiple linear regression is a data analysis technique used in this study. Based on the results of data analysis, several conclusions can be drawn as follows: Company growth, profitability, Capital Structure simultaneously influence company value in Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Company growth has no partial effect on company value in Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Profitability has a partial effect on company value in Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Capital Structure has no partial effect on company value in Food and Beverage Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2019 period 2021Keywords: Indonesia Stock Exchange, Firm Value, profitability and capital structure